2014
DOI: 10.1111/ddg.12405_suppl
|View full text |Cite
|
Sign up to set email alerts
|

Kompressionstherapie – Kenntnisse und Anwendungspraxis

Abstract: Clearly, compression material and its application are unfamiliar to most practice employees. Without question there are deficits in the provision of compression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
7

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
0
10
0
7
Order By: Relevance
“…Scarcely one in ten persons could meet the requirement of achieving a pressure value in the range of 50 to 60 mmHg. The large majority of 77 % laid below this target value (17).…”
Section: Scientific Principles and Reality Of Treatmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Scarcely one in ten persons could meet the requirement of achieving a pressure value in the range of 50 to 60 mmHg. The large majority of 77 % laid below this target value (17).…”
Section: Scientific Principles and Reality Of Treatmentmentioning
confidence: 97%
“…Up to 61 % of patients with a florid VLU receive no compression therapy (13)(14)(15)(16). Furthermore, data from the cross-sectional study "Compression therapy -scientific background and practical applications" conducted throughout Germany, show that many of the professional groups involved in the care of persons with a VLU have insufficient knowledge of the available compression materials and are also unfamiliar with their features (17).…”
Section: Scientific Principles and Reality Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In nursing school, the curriculum on average provides for 1–2 hours to be spent on compression therapy. In medical school, this topic is rarely taught . A cross‐sectional study revealed that only one‐half of patients wearing short‐stretch bandages had a bandage that was “adequately wrapped” .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to users (e.g. nurses, doctors), too, there was only limited knowledge regarding compression materials currently available as well as their use . Of 891 participants, only 15 % knew about multi‐component systems or ulcer stockings.…”
Section: Introductionmentioning
confidence: 99%